Mobile Learning Model for the Zimbabwe Higher Education Sector - Maketo, Lydia (Curtin University, 2020)
Mobile learning involves mobile learners utilising mobile technologies to extend learning. This research aims to develop a model for mobile learning for Zimbabwe universities. Mobile learning in higher education is an under researched topic in developing countries. This comprehensive research takes a mixed-method approach comprising interviews, focus group discussions and a survey to critically evaluate the model. The research outcomes are a new m-learning model for Zimbabwe higher education and practical recommendations.